Physicochemical and functional characteristics of flour and starch from breadfruit (Artocarpus altilis) and its resistant starch fermentation properties - Siti Nuriah binti Mohd Noor
Breadfruit (Artocarpus altilisi or sukun is a Malaysian traditional food crop that is commonly harvested for their pulp as a food. However, due to poor storability of the fresh fruits, thus limited its research and industrial applications. This study aims to determine the physicochemical properties of breadfruit flour and starch, to identify the suitable processing conditions for the production of breadfruit resistant starch type III (BFRS3) and to assess the fermentability of HCI-breadfruit resistant starch type III (HCI-BFRS3) by lactic acid bacteria (LAB); Lactobacillus plantarum (ATCC® 13649) and Lactobacillus brevis (ATCC® 8287) against the detrimental bacterium, Escherichia coli (ATCC® 11775). Mature breadfruits were harvested and processed into flour, starch and resistant starch type III (RS3). The physicochemical properties were determined for breadfruit flour and starch, respectively. Eight (8) processing conditions of the breadfruit starch which involved starch gelatinization, enzymatic debranching of starch polymer, retrogradation and drying were conducted during the production of BFRS3. The purification of BFRS3 was done using acid hydrolysis to produce HCI-BFRS3. The fermentability of HCI-BFRS3 was assessed using selected LAB. Breadfruit flour and starch exhibited highest in ash and crude fibre; 2.25%, 4.85% and 0.86%, 2.89%, respectively. Breadfruit flour contained 63.71% of total starch content with a 33:67 ratio of amylose and amylopectin. The swelling power and solubility increased with temperatures as well as water and oil holding capacities also higher were recorded for breadfruit flour and starch. Breadfruit flour granules were spherical, indented with umbilical point appeared at the center and average sizes of 5 to 10 urn. Breadfruit starch has larger granules (8 to 10 urn) than its flour, indented with smooth and retained granular structure. Breadfruit flour displayed a B-type crystal with gelatinization temperature (Te) and enthalpy gelatinization (~H) of 77.01 °C and 4.83 Jig. BFRS3 with highest resistant starch (RS) content, 54.59% was produced when the breadfruit starch suspended in distilled water and gelatinized by boiling at 90°C for 30 minutes, debranched with pullulanase enzyme at 60°C for 24 hours, autoclaved at 1210C for 1 hour and stored cold at 4°C for 24 hours. Purification ofBFRS3 with 0.5 M HCI acid at 60°C for 24 hours (denoted as HCI-BFRS3) has increased the RS content up to 57.86%. HCI-BFRS3 granules had a rougher outer surface than breadfruit starch and BFRS3. HCI-BFRS3 has higher T, (79.73°C), ~H (14.64 Jig) and smaller transition temperature range, Tc- To (4.28°C) as compared to breadfruit starch. HCI-BFRS3 was further assessed for in- vitro fermentation. HCI-BFRS3 has supported the growth of L. plantarum and L. brevis, also reduced the pH of fermentation medium with 0.34 and 0.26 respectively. The highest prebiotic activity score (PAS) was obtained by L. plantarum at 24 hours fermentation compared to the positive control (inulin and fibersol-2). From this study, breadfruit flour and starch possessed different physicochemical properties which made it distinguished from each other and the HCI BFRS3 exhibited ability to be fermented by selected LAB. Thus, HCI-BFRS3 has potential as a prebiotic material that worth to be explored as a functional food ingredient in the food industry.